A Controlled Pre-Post Evaluation of a Computer-based HIV/AIDS Education on Students’ Sexual Behaviors, Knowledge and Attitudes - Musiimenta, Angella (Online Journal of Public Health Informatics, 2012)
Unlike traditional approaches to sexuality and HIV education which can be constrained by the sensitive nature of the subject, Information Technology (IT) can be an innovative teaching tool that can be used to educate people about HIV. This is especially relevant to interventions targeting young people; the population group fond of using IT, and the same group that is more vulnerable to HIV/AIDS. Yet, there are significantly few empirical studies that rigorously evaluated computer-assisted school-based HIV/AIDS interventions in developing countries. The modest studies conducted in this area have largely been conducted in developed countries, leaving little known about the effectiveness of such interventions in low resource settings, which moreover host the majority of HIV/AIDS infections. This research addresses this gap by conducting a controlled pre-post intervention evaluation of the impacts of the World Starts With Me (WSWM), a computer-assisted HIV/AIDS intervention implemented in schools in Uganda. The research question was: did the WSWM intervention significantly influence students’ sexual behaviors, HIV/AIDS knowledge, attitudes and self-efficacy? To address this question, questionnaires were simultaneously administering to 146 students in an intervention group (the group receiving the WSWM intervention) and 146 students in a comparison group (the group who did not receive the WSWM intervention), before (February 2009) and after the intervention (December 2009). Findings indicate that the intervention significantly improved students’ HIV/AIDS knowledge, attitudes self-efficacy, sex abstinence and fidelity, but had no significant impact on condom use. The major reason for non-use of condoms was lack of knowledge about condom use which can be attributed to teachers’ failure and inabilities to demonstrate condom use in class. To address this challenge, intervention teachers should be continuously trained in skills-based and interactive sexuality education. This training will equip them with self-confidence and interactive teaching skills, including tactics for emphasizing building students’ skills through role plays and interactive assignments. In addition, the HIV interventions themselves should include interactive virtual condom use demonstrations that can be accessed by students themselves.
Keywords: ICT for HIV/AIDS; WSWM; Sexual behaviors; Knowledge and attitudes; School